Medical and Rehabilitation Centers in Children's Houses - New Opportunities for Treatment and Rehabilitation of Children - I.V. Balychevtseva; V.B. Visyagin; N.V. Schur (Zaslavsky O.Yu., 2014)
The article presents data on the opening of medical and rehabilitations centers at the children's houses of Donetsk region. Approaches, terms, possibilities and methods of rehabilitations used during the treatment and restoration of disabled children are provided.